Students’ Perception of the Use of Youtube in English Language Learning - Tania Tahmina (Journal of Languages and Language Teaching, 2023)
Digital learning has become a new learning mode in higher education.  Learners have become heavily dependent on YouTube channels and other technology-enhanced language learning platforms. As the YouTube platform has become an inexorable part of students’ lives, language teachers can explore their perceptions and assist them to learn English language with the help of this platform. This study aimed to find out the learners’ perception of using YouTube as a learning medium to enhance their language learning. In addition, a few pedagogical implications will also be provided. The research respondents comprised sixty-six undergraduate students of the Department of English, Jagannath University, Dhaka, Bangladesh. The data were collected using a questionnaire and semi-structured interviews. The findings revealed that the majority of the students reported that they benefitted by watching YouTube educational videos; however, in preparing assignments, being attentive while studying, and acquiring grammatical competence, learners reported that this platform had little impact. Most of the students reported that YouTube helped them to learn English vocabulary, to make learning English very interesting, to comprehend the contents of YouTube videos in a very easy manner, get relevant materials to learn English language, acquire English language better by writing down the major points in a diary while watching videos, to develop speaking skills watching YouTube videos, and to enhance listening comprehension. Therefore, based on the findings of this study, it can be concluded that the use of YouTube has numerous positive impacts on EFL learners’ English language proficiency.